Chiefdoms under siege Spain's rule and native adaptation in the southern Colombian Andes, 1535 - 1700 - Calero, Luis Fernando (Univ. of New Mexico Press, 1997)
"A disappointing study of the Pastos, Quillacingas, and Abads in Southern Colombia between 1535-1700. Chapters focus on precolumbian inhabitants, ecology, Spanish land acquisition, colonial labor and tribute impositions, and the encomienda. Although based on several data-filled visitas, text is riddled with problems, ranging from unsupported interpretations to factual errors"--Handbook of Latin American Studies, v. 58.. - http://www.loc.gov/hlas/